(5, 6)-Connected 3D Metal–Organic Framework Based on Terphenyl-3, 2″, 5″, 3′-tetracarboxylate: Synthesis, Structures, and Properties. Issue 9 (1st September 2016) - Wang, Hua-Rui; Liu, Shi-Jiang
Abstract : One metal–organic framework [Mn(tptc)0.5 (bpp)] (1 ) (H4 tptc = terphenyl-3, 2″, 5″, 3′-tetracarboxylic acid, bpp = 1, 3-bis(4-pyridyl)propane) has been synthesized by the reaction of a tetracarboxylate and auxiliary pyridine-based ligands with Mn(II) ion under hydrothermal conditions. This complex was further studied by elemental analysis, IR spectroscopy, and X-ray crystallography. In the structure of1, the alternately assembled 2D helical bilayers and pyridine pillars gives rise to a rare (5, 6)-connected 3D pillared helical-layer MOF. In addition, thermal gravimetric analysis of1 was also investigated.